Assessment of the Performance of Solid Phase Extraction Based on Pipette Tip Employing a Hybrid Molecularly Imprinted Polymer as an Adsorbent for Enantioselective Determination of Albendazole Sulfoxide. (20th April 2019) - Anacleto, Sara da Silva; de Oliveira, Hanna Leijoto; da Silva, Anny Talita Maria; do Nascimento, Tienne Aparecida; Borges, Marcella Matos Cordeiro; Silva, Ricky Cássio dos Santos; Pereira, Arnaldo César; Borges, Keyller Bastos
Abstract: Herein, an organic–inorganic hybrid molecularly imprinted polymer (MIP) was successfully synthesized with albendazole sulfoxide (ABZSO) as a template and 3-(trimethoxysilyl)propyl methacrylate, a bifunctional group compound, as a single cross-linking agent. In this study, a simple method using HPLC–DAD was developed for the determination of ABZSO enantiomers in human urine using pipette tip-based molecularly imprinted polymer solid phase extraction (PT–MIP–SPE). Enantioseparation with satisfactory retention times (5.17 and 7.09 min), acceptable theoretical plates ( N = 4, 535 and 5, 091) and strong resolution ( R s = 5.45) was performed with an Agilent® Eclipse Plus C18 (100 mm × 4.6 mm, 3.5 μm) coupled with a Chiralpak® IA column (100 mm × 4.6 mm, 3 μm), a mixture with ethanol:water (50:50, v/v) as the mobile phase, temperature at 40°C, flow rate at 0.9 mL min −1 and λ = 230 nm. Thereafter, certain parameters affecting the PT–MIP–SPE were investigated in detail and the better conditions were: 300 μL of water as washing solvent, 500 μL of ethanol:acetic acid (9:1, v/v ) as eluting solvent, 20 mg of MIP, 500 μL of human urine at pH 9 and no addition of NaCl. Recoveries/relative standard deviation (RSD%) for (R)-(+)-ABZSO and (S)-(−)-ABZSO were 78.2 ± 0.2% and 69.7 ± 1.7%, respectively.